Ileal amino acid digestibility in micronized full fat soybean meal and textured soy flour fed to piglets with or without multicarbohydrase and phytase supplementation - Dadalt, J. C.; Gallardo, C.; Polycarpo, G. V. [UNESP]; Berto, D. A. [UNESP]; Trindade Neto, M. A. (Elsevier, 2017)
Most amino acid (AA) digestibility values for feed ingredients are obtained using ileal-cannulated pigs. The ileal-cannulated pig model is not used with pigs younger than six weeks of age due to difficulties related to T-cannula implantation in the distal ileum and potential problems related to post-surgical recovery. Thus, the present experiment aimed to determine the digestibility of two ingredients in young pigs using the slaughter method. Fifty 23-d-old weaned pigs were divided into two experiments to evaluate the apparent total tract digestibility (ATTD) and apparent (AID) and standardized (SID) ileal amino acid digestibility in micronized full fat soybean meal (MFFS) and textured soy flour (TS) with or without phytase (Phy) and multi-carbohydrase (MC) supplementation. Each piglet was individually housed in a metabolic cage in a completely randomized experimental design with a 2 × 2 factorial arrangement of treatments to determine the effects of MC (0 and 0.2%) and Phy (0 and 0.05%). During the first 8 d, a diet was formulated to meet or exceed nutrient specifications for piglets. Subsequently, the animals were introduced to experimental diets for 10 d (a 6-d adaptation period followed by a 4-d faeces and urine total collection). A corn/dry-whey/milk-powder diet was used as a reference diet (RD). Ileal digesta was collected at slaughter (45 d of age) after a 4-d adaptation period with a low protein diet (5% casein). There was no effect of MC or Phy supplementation on nutrient and energy digestibility in MFFS. The SID of AA in MFFS without enzymes was on average 6% lower than in published data in the literature (NRC, 2012). Similarly, in TS, no interactions (P > 0.05) between enzymes were observed on AID or SID of essential AA. However, Phy supplementation improved the ATTD of crude protein (CP) and the SID of Arg, His, Glu and Pro (P < 0.05), while MC improved the SID (P < 0.01) of His, Cys, Glu, and Gly. It was difficult to compare these results with values from literature due to a lack of information regarding TS. As hypothesized, the results of experiments reported here suggest that the digestibility of nutrients and energy in MFFS is lower compared with literature values. However, since digestibility of raw materials differs from batch to batch and from experiment to experiment, more researches should be conducted to compare the digestibility of ingredients for piglets in different ages.
Keywords: Amino acid; Apparent digestibility; Enzymes; Soybean products; Standardized digestibility